2011
DOI: 10.1001/jama.2011.1654
|View full text |Cite
|
Sign up to set email alerts
|

Number of Coronary Heart Disease Risk Factors and Mortality in Patients With First Myocardial Infarction

Abstract: Context Few studies have examined the association between the number of coronary heart disease risk factors and outcomes of acute myocardial infarction in community practice. Objective To determine the association between the number of coronary heart disease risk factors in patients with first myocardial infarction and hospital mortality. Design Observational study from the National Registry of Myocardial Infarction, 1994-2006. Patients We examined the presence and absence of 5 major traditional coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
158
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(187 citation statements)
references
References 17 publications
(29 reference statements)
21
158
0
8
Order By: Relevance
“…(16) AMI is one of the leading causes of mortality worldwide. (17,18) The results of the current study indicate that, after adjustment for potential confounding factors, hip fracture is independently associated with a 29% increase in risk of developing AMI compared with controls. In addition, the risk of AMI after hip fracture is more prominent in elderly patients, women, and in patients with other underlying diseases.…”
Section: Discussionmentioning
confidence: 59%
“…(16) AMI is one of the leading causes of mortality worldwide. (17,18) The results of the current study indicate that, after adjustment for potential confounding factors, hip fracture is independently associated with a 29% increase in risk of developing AMI compared with controls. In addition, the risk of AMI after hip fracture is more prominent in elderly patients, women, and in patients with other underlying diseases.…”
Section: Discussionmentioning
confidence: 59%
“…Our results indicate a secondary prevention benefit of ideal cardiovascular health status in midlife, which further supports the promotion of cardiovascular health on the basis of Life's Simple 7. Our results seem critically important because previous studies focusing on health factors at MI admission reported, counterintuitively, that “better” health status led to poorer MI prognosis 3, 4, 5. Although our data do not have information on Life's Simple 7 factors at the time of MI admission, there may be a few explanations for this counterintuitive relationship.…”
Section: Discussionmentioning
confidence: 53%
“…To complicate this question, a few studies have reported that a higher number of traditional risk factors at admission was counterintuitively associated with lower in‐hospital mortality in patients with myocardial infarction (MI) 3, 4, 5. However, these studies retrospectively collected information on traditional risk factors at or before MI diagnosis, mainly relying on medication use for defining hypertension, diabetes mellitus, and dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…For current smoking, interestingly, a few studies reported that their presence (together with other traditional atherosclerotic risk factors such as dyslipidemia) was counterintuitively associated with better prognosis among patients with MI 35, 36, 37. Although the exact reasons are not clear, investigators from those studies made several speculations.…”
Section: Discussionmentioning
confidence: 99%